A miR‐29a‐driven negative feedback loop regulates peripheral glucocorticoid receptor signaling. Issue 5 (11th February 2019) - Glantschnig, Christina; Koenen, Mascha; Gil‐Lozano, Manuel; Karbiener, Michael; Pickrahn, Ines; Williams‐Dautovich, Jasmine; Patel, Rucha; Cummins, Carolyn L.; Giroud, Maude; Hartleben, Götz; Vogl, Elena; Blüher, Matthias; et al.
ABSTRACT: The glucocorticoid receptor (GR) represents the crucial molecular mediator of key endocrine, glucocorticoid hormone–dependent regulatory circuits, including control of glucose, protein, and lipid homeostasis. Consequently, aberrant glucocorticoid signaling is linked to severe metabolic disorders, including insulin resistance, obesity, and hyperglycemia, all of which also appear upon chronic glucocorticoid therapy for the treatment of inflammatory conditions. Of note, long‐term glucocorticoid exposure under these therapeutic conditions typically induces glucocorticoid resistance, requiring higher doses and consequently triggering more severe metabolic phenotypes. However, the molecular basis of acquired glucocorticoid resistance remains unknown. In a screen of differential microRNA expression during glucocorticoid‐dependent adipogenic differentiation of human multipotent adipose stem cells, we identified microRNA 29a (miR‐29a) as one of the most down‐regulated transcripts. Over‐expression of miR‐29a impaired adipogenesis. We found that miR‐29a represses GR in human adipogenesis by directly targeting its mRNA, and downstream analyses revealed that GR mediates most of miR‐29a's anti‐adipogenic effects. Conversely, miR‐29a expression depends on GR activation, creating a novel miR‐29‐driven feedback loop. miR‐29a and GR expression were inversely correlated both in murine adipose tissue and in adipose tissue samples obtained from human patients. In the latter, miR‐29a levels were additionally strongly negatively correlated with body mass index and adipocyte size. Importantly, inhibition of miR‐29 in mice partially rescued the down‐regulation of GR during dexamethasone treatment. We discovered that, in addition to modulating GR function under physiologic conditions, pharmacologic glucocorticoid application in inflammatory disease also induced miR‐29a expression, correlating with reduced GR levels. This effect was abolished in mice with impaired GR function. In summary, we uncovered a novel GR‐miR‐29a negative feedback loop conserved between mice and humans, in health and disease. For the first time, we elucidate a microRNA‐related mechanism that might contribute to GR dysregulation and resistance in peripheral tissues.—Glantschnig, C, Koenen, M., Gil‐Lozano, M., Karbiener, M., Pickrahn, I., Williams‐Dautovich, J., Patel, R., Cummins, C. L., Giroud, M., Hartleben, G., Vogl, E., Blüher, M., Tuckermann, J., Uhlenhaut, H., Herzig, S., Scheideier, M. A. miR‐29a–driven negative feedback loop regulates peripheral glucocorticoid receptor signaling. FASEB J. 33, 5924–5941 (2019). www.fasebj.org